2015
DOI: 10.1007/s11205-015-1170-8
|View full text |Cite
|
Sign up to set email alerts
|

What Predicts Adolescent Delinquent Behavior in Hong Kong? A Longitudinal Study of Personal and Family Factors

Abstract: Using four waves of data from Secondary 1 to Secondary 4 (N = 3328 students at Wave 1), this study examined the development of delinquent behavior and its relationships with economic disadvantage, family non-intactness, family quality of life (i.e., family functioning) and personal well-being (i.e., positive youth development) among Hong Kong adolescents. Individual growth curve models revealed that delinquent behavior increased during this period, and adolescents living in non-intact families (vs. intact fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 84 publications
2
24
0
Order By: Relevance
“…In view of the inadequate empirical research as well as equivocal findings, there is a need to further determine the causal effect of problem behaviors on LS among adolescents. This is especially important for early adolescents because of the well-documented decline in LS and increase in maladaptive behaviors during early adolescence (Shek and Lin 2016;Patel et al 2007). Furthermore, Lyons et al (2013) suggested self-reported externalizing behaviors might be more stable in comparison to internalizing behaviors, thus exerted more persistent impacts on LS.…”
Section: Negative Impacts Of Maladaptive Behavior On Lsmentioning
confidence: 99%
“…In view of the inadequate empirical research as well as equivocal findings, there is a need to further determine the causal effect of problem behaviors on LS among adolescents. This is especially important for early adolescents because of the well-documented decline in LS and increase in maladaptive behaviors during early adolescence (Shek and Lin 2016;Patel et al 2007). Furthermore, Lyons et al (2013) suggested self-reported externalizing behaviors might be more stable in comparison to internalizing behaviors, thus exerted more persistent impacts on LS.…”
Section: Negative Impacts Of Maladaptive Behavior On Lsmentioning
confidence: 99%
“…Similar to previous research (Shek and Lin 2016), family intactness was evaluated using marital status of participants' parents. A total of 370 (85.25%) participants who reported that their parents were in the first marriage were categorized into the group with intact family, and 64 (14.75%) participants whose parents were divorced, separated or in their second marriage were categorized into the non-intact family group.…”
Section: Family Intactnessmentioning
confidence: 99%
“…For instance, in Geldhof et al’s (2014) longitudinal study involving American students from Grade 5–12 (i.e., eight waves), PYD assessed as five Cs (i.e., competence, confidence, connection, character and caring) was inversely related to delinquency and substance use in all waves. Likewise, in a large-scale study which defined PYD in terms of 15 developmental assets (e.g., resilience, behavioral competence, moral competence, emotional competence, and spirituality), Shek and collaborators found that PYD had inverse concurrent and longitudinal associations with externalizing problem behaviors among Chinese adolescents ( Sun and Shek, 2012 ; Shek and Lin, 2016a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…However, relatively fewer studies attempted to uncover the relationship between the PYD attributes and the rate of change in adolescent problem behaviors. Among those who did, Shek and Lin (2016a , b ) investigated how initial general PYD attributes encompassing the 15 developmental assets predicted the growth rate of delinquency over time. However, no research has to date been conducted to examine how specific developmental assets are related to the growth rate of risk and delinquent behavior and problem behavioral intention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation